2002
DOI: 10.1002/chir.10105
|View full text |Cite
|
Sign up to set email alerts
|

First direct discrimination of chiral phosphine selenide (P=Se) derivatives by multinuclear magnetic resonance spectroscopy in the presence of a chiral dirhodium complex

Abstract: Enantiomeric ratios of compounds with P=Se functionalities (phosphine selenides) can easily be determined by (1)H, (13)C, (31)P, and (77)Se NMR spectroscopic inspection of their diastereomeric complexes with (R)-Rh(2)(MTPA)(4) (MTPA-H identical with methoxytrifluoromethylphenylacetic acid; Mosher's acid). This is the first facile and rapid spectroscopic method for chiral recognition in this class of compounds. Whereas most complexation shifts Delta(delta) are moderate or even negligible, significant signal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…8 Very recently, we reported that phosphines (R 1 R 2 R 3 P) form long-lived adducts with Rh* at room temperature so that 103 Rh, 31 P couplings give rise to 31 P signal splitting. 9,10 This is in sharp contrast to all other ligands studied previously, including phosphine chalcogenides, 6,11 where the individual adducts may be observable only at low temperatures. 12 In the present study, we report on the extension of our studies to secondary phosphine oxides 1-6 (Scheme 1) which are regarded as convenient precursors to synthesize a variety of valuable organophosphorus compounds as well as ligands per se.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…8 Very recently, we reported that phosphines (R 1 R 2 R 3 P) form long-lived adducts with Rh* at room temperature so that 103 Rh, 31 P couplings give rise to 31 P signal splitting. 9,10 This is in sharp contrast to all other ligands studied previously, including phosphine chalcogenides, 6,11 where the individual adducts may be observable only at low temperatures. 12 In the present study, we report on the extension of our studies to secondary phosphine oxides 1-6 (Scheme 1) which are regarded as convenient precursors to synthesize a variety of valuable organophosphorus compounds as well as ligands per se.…”
mentioning
confidence: 67%
“…The CDCl 3 solutions always contain a small portion of acetone-d 6 for the sake of better solubility of Rh*.…”
Section: Deuterium Exchange and Isotope Effectsmentioning
confidence: 99%
See 3 more Smart Citations